Zirconium tin lanthanum barium strontium lead titanate ceramic with high strontium doping amount as well as preparation method and application of zirconium tin lanthanum barium strontium lead titanate ceramic

Through the preparation of lanthanum barium strontium lead ceramics with high strontium doping, the microstructure of the ceramics is optimized by using traditional solid-phase reaction method and casting molding process, and the insufficient energy storage density of existing antiferroelectric ceramic materials is solved. Problem, high energy storage density and high efficiency electrical performance are achieved, suitable for pulse power devices.

CN119263826APending Publication Date: 2025-01-07GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411210477.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing antiferroelectric ceramic materials have shortcomings in improving energy storage density, especially in high-power pulse discharge applications, where the performance of the materials has not yet achieved satisfactory improvement.

Method used

Using high strontium doping zirconium tin lanthanum barium strontium lead ceramic (Pb0.92-xLa0.04SrxBa0.02) (Zr0.64Sn0.35Ti0.01)O3, the traditional solid phase reaction method, casting molding process and two Preparation of subsintering process to optimize the microstructure and electrical properties of ceramics.

Benefits of technology

High energy storage density and high energy storage efficiency are achieved, specifically manifested as Pb0.84La0.04Sr0.06Ba0.02Zr0.64Sn0.35Ti0.01O3 ceramic has an energy storage density of 11.16J/cm3 and an energy storage efficiency of 96.23%, suitable for pulses Power devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263826A_ABST
    Figure CN119263826A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of dielectric materials, and discloses zirconium tin lanthanum barium strontium lead titanate ceramic with high strontium doping amount and a preparation method and application thereof. The molecular formula of the zirconium tin lanthanum barium strontium lead titanate ceramic with the high strontium doping amount is (Pb < 0.92-x > La < 0.04 > Sr < x > Ba < 0.02 >) (Zr < 0.64 > Sn < 0.35 > Ti < 0.01 >) O3, x is 0.04-0.1, the ceramic has high energy storage density and energy storage efficiency, when x is 0.06, the energy storage density of the Pb < 0.84 > La < 0.04 > Sr < 0.06 > Ba < 0.02 > Zr < 0.64 > Sn < 0.35 > Ti < 0.01 > O3 ceramic is 11.16 J / cm < 3 >, the energy storage efficiency of the Pb < 0.84 > La < 0.04 > Sr < 0.06 > Ba < 0.02 > Zr < 0.64 > Sn < 0.35 > Ti < 0.01 > O3 ceramic is 96.23%, and the ceramic can be applied to pulse power devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of dielectric materials, and in particular, relates to a high-strontium-doped lanthanum zirconium-tin-barium-strontium-lead titanate ceramic and a preparation method and application thereof. Background Art

[0002] With the rapid development of industrialization and urbanization, the global demand for energy has increased dramatically. Traditional fossil energy is not only limited in resources, but also has serious impacts on the environment due to the greenhouse gases and pollutants produced during combustion. Therefore, the development and utilization of clean energy has become a top priority. Dielectric capacitors can play an important role in the storage and release of energy. As a high-performance dielectric material, the research background of antiferroelectric ceramics is mainly based on its unique electric field-induced antiferroelectric-ferroelectric phase transition characteristics, which provides broad prospects for the application of materials in high-power pulse discharge capacitors, energy storage devices and other fields. Antiferroelectrics have the potential for high energy storage density due to their double hysteresis loops and remnant polarization intensity close to zero. In the field of energy storage, the research progress of antiferroelectric ceramics mainly focuses on improving energy storage performance and reducing the applied electric field intensity.

[0003] The working mechanism of antiferroelectric (AFE) capacitors is based on the unique double hysteresis loop properties of antiferroelectric materials. Antiferroelectric materials can undergo a phase transition from antiferroelectric phase to ferroelectric phase under the action of an external electric field, accompanied by significant changes in electrostrain and polarization intensity. This phase transition process makes AFE capacitors have the characteristics of high energy storage density and high power density, suitable for high-power pulse discharge applications. There are many types of known antiferroelectric materials, such as lead zirconate (PbZrO3), lead hafnium oxide (PbHfO3), silver niobate (AgNbO3), sodium niobate (NaNbO3), etc. Lead zirconate (PbZrO3), as the earliest discovered antiferroelectric material, has a perovskite structure with high structural stability and is widely used in energy storage capacitors and voltage regulation elements. In order to significantly improve the performance of PbZrO3, especially in terms of improving energy storage density. By doping La 3+ , Ba 2+ , Sr 2+ , Ca 2+ Sn 4+ 、Ti 4+ Plasma chemical modification has developed many different material systems, such as (Pb, La)(Zr, Ti)O 3、 (Pb,La)(Zr,Sn,Ti)O3, (Pb,La)(Zr,Sn)O3, Pb[Nb(Zr,Sn,Ti)]O3, etc. Ceramics with high energy storage performance can be obtained through reasonable chemical modification and good sintering methods. Summary of the invention

[0004] The present invention aims at solving the problems existing in the prior art and has the primary purpose of providing a high strontium-doped zirconium-tin-barium-strontium-lead titanate lanthanum ceramic.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned lanthanum barium strontium lead zirconium tin titanate ceramic with high strontium content.

[0006] Another object of the present invention is to provide an application of the above-mentioned lanthanum barium strontium lead zirconium tin titanate ceramics with high strontium doping.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] The molecular formula of a high strontium-doped zirconium-tin-barium-strontium-lead titanate lanthanum is (Pb 0.92-x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 )O3,x=0.04~0.1.

[0009] The method for preparing the high strontium-doped zirconium-tin-barium-strontium-lead titanate lanthanum ceramic comprises the following steps:

[0010] S1. PbO, La2O3, SrCO3, BaCO3, ZrO2, SnO2, TiO2 and excess 3-5wt% PbO were wet-milled in a common planetary ball mill, and ethanol and a milling medium were added to obtain a slurry;

[0011] S2. The slurry is dried at 80 to 120 ° C, sieved after grinding, and then pre-fired at 850 to 950 ° C to obtain a ceramic powder;

[0012] S3. The ceramic powder is ball-milled, dried and sieved according to steps S1 and S2, and the obtained powder is rolled with octylphenol polyoxyethylene ether and solvent to obtain a premixed slurry; polyvinyl butyral, solvent and trioctyl trimellitate are then added and rolled to obtain a casting slurry with a viscosity of 600 to 800 mPa·s.

[0013] S4. The casting slurry is placed in a mold, the linear speed of the casting machine film belt is 0.15-0.3 cm / s, the drying temperature is 35-42°C, the binder is removed at 300-600°C, and finally sintered at 1100-1200°C to obtain lanthanum barium strontium lead zirconium tin titanate ceramics, abbreviated as PLSBZST.

[0014] Preferably, the ball milling media in step S1 are zirconium dioxide balls with a diameter of 2 to 3 mm and zirconium dioxide balls with a diameter of 4 to 5 mm in a mass ratio of 1:1.

[0015] Preferably, the ball milling speed in step S1 is 180-220 rpm, and the ball milling time is 24-48 h.

[0016] Preferably, the mesh size of the sieving in step S2 is 40 to 80 meshes, the drying time is 5 to 10 hours, and the pre-burning time is 2 to 3 hours.

[0017] Preferably, the solvents in step S3 are anhydrous ethanol and butanone in a mass ratio of 1:1.

[0018] Preferably, the mass ratio of the powder, octylphenol polyoxyethylene ether, solvent, polyvinyl butyral and trioctyl trimellitate in step S3 is (45-50):(0.8-0.9):(58-60):(5.3-5.5):(1.8-2).

[0019] Preferably, the rotation speed of the tumbling in step S3 is 100-200 rpm, and the tumbling time is 18-24 h.

[0020] The application of the high strontium doped zirconium tin titanate lanthanum barium strontium lead ceramic in the field of dielectric energy storage capacitors.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention obtains ceramic (Pb 0.92-x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 )O3(x=0.04~0.1). The ceramic has high energy storage density and energy storage efficiency. When x=0.06, Pb 0.84 La 0.04 Sr 0.06 Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 The energy storage density of O3 ceramics is 11.16 J / cm 3 And the energy storage efficiency is 96.23%, which can be applied in pulse power devices.

[0023] 2. The present invention uses a traditional solid phase reaction method, a tape casting process and a secondary sintering process to prepare lanthanum zirconium tin titanate lead strontium barium ceramics. The method uses a traditional solid phase reaction to obtain a high-purity PLSBZST ceramic powder without subsequent treatment. The tape casting process can obtain a small, flat and uniform ceramic body, and the secondary sintering method can obtain a small and uniform microstructure, which is beneficial to improve the breakdown electric field strength of the PLSBZST thick film ceramic, thereby improving the energy storage performance of the PLSBZST ceramic. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Pb obtained in Example 1-4 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 Room temperature X-ray diffraction pattern of O3 ceramics.

[0025] Figure 2 Pb obtained in Example 1-4 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 Scanning electron microscope (SEM) image of O3 ceramics;

[0026] Figure 3 The (Pb 0.92-x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 ) The dielectric constant and dielectric loss of O3 ceramics at 1kHz vary with temperature (a) and the dielectric constant and dielectric loss of PLSBZST2 vary with temperature and frequency (b);

[0027] Figure 4 Pb obtained in Example 1-4 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 PE and IE curves of O3 ceramics;

[0028] Figure 5 Pb obtained in Example 1-4 0.92-x La 0.04 Sr xBa 0.02 Zr 0.64 Sn 0.35 Ti 0.01 Dischargeable energy density and energy storage efficiency of O3 ceramics under electric field.

[0029] Figure 6 is the Pb of Examples 1-4 at 10 Hz 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 Room temperature PE hysteresis loop of O3 ceramics;

[0030] Figure 7 The different Sr prepared in Examples 1-4 2+ The discharge energy density W obtained by the hysteresis loop of the PLSBZST ceramics under the transition electric field of each component ceramic rec and energy storage efficiency ηFig. DETAILED DESCRIPTION

[0031] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0032] In the embodiments of the present invention, PbO, La2O3, SrCO3, BaCO3, ZrO2, SnO2, and TiO2 (all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were used for crystal structure analysis in material structure characterization and performance testing using a DMAX-UltimaIV X-ray diffractometer (XRD) from Rigaku Corporation of Japan. A Hitachi S-3400 (II) scanning electron microscope (SEM) was used for surface morphology analysis. Agilent E49840A precision impedance analyzer was used for dielectric properties. Multiferroic ferroelectric comprehensive test system from Radiant Corporation of the United States was used for ferroelectric properties.

[0033] Example 1

[0034] 1. PbO, La2O3, SrCO3, BaCO3, ZrO2, SnO2, and TiO2 were weighed according to the stoichiometric ratio and placed in a 250 mL nylon ball mill. An excess of 3 wt% PbO was then added to compensate for the volatilization of Pb during high temperature sintering;

[0035] 2. Use a common planetary ball mill for wet ball milling, add ethanol and ball milling media (3 mm and 5 mm zirconium dioxide balls in a mass ratio of 1:1), rotate at 180-220 rpm, and ball milling for more than 24 hours to obtain a slurry;

[0036] 3. The slurry was placed in an oven and dried at 120°C for 5 hours, ground in an agate mortar, passed through 40-mesh and 80-mesh sieves in sequence, and then pre-calcined at 920°C for 2 hours to obtain ceramic powder;

[0037] 4. The ceramic powder is ball-milled and dried and sieved according to steps 2 and 3. The obtained ceramic powder (about 50 g) is placed in a rolling mill, 0.9 g of a dispersant (octylphenol polyoxyethylene ether) and 40 g of a solvent (anhydrous ethanol and butanone in a mass ratio of 1:1) are added, and then rolling milled at a speed of 200 rpm for more than 24 hours to obtain a premixed slurry; 1.5 g of a binder (polyvinyl butyral) is added and rolling milled at a speed of 200 rpm for more than 18 hours; then 18 g of a solvent (anhydrous ethanol and butanone in a mass ratio of 1:1), 4 g of a binder (polyvinyl butyral) and 2 g of a plasticizer (trioctyl trimellitate) are added and ball-milled at a speed of 200-250 rpm for more than 24 hours to obtain a uniformly mixed casting slurry with a viscosity of 600-800 mPa·s.

[0038] 5. The casting slurry is placed in a mold, the casting machine film belt linear speed is about 0.15-0.3 cm / s, the drying temperature is 35-42 ° C, the binder is removed at 300 ° C for 0.5 h, the binder is removed at 600 ° C for 7 h, and finally sintered at 1160 ° C for 2 h to obtain zirconium tin titanate lanthanum barium strontium lead ceramics, whose molecular formula is (Pb 0.92-x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 )O3(x=0.04), abbreviated as PLSBZST1.

[0039] Example 2

[0040] The difference from Example 1 is that the molecular formula of the zirconium tin titanate lanthanum barium strontium lead ceramic is (Pb 0.92- x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 )O3(x=0.06), abbreviated as PLSBZST2.

[0041] Example 3

[0042] The difference from Example 1 is that the molecular formula of the zirconium tin titanate lanthanum barium strontium lead ceramic is (Pb 0.92- x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 )O3(x=0.08), abbreviated as PLSBZST3.

[0043] Example 4

[0044] The difference from Example 1 is that the molecular formula of the zirconium tin titanate lanthanum barium strontium lead ceramic is (Pb 0.92- x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 )O3(x=0.1), abbreviated as PLSBZST4.

[0045] Figure 1 Pb obtained in Example 1-4 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 Room temperature X-ray diffraction pattern of O3 ceramics. Figure 1 It can be seen that the diffraction peaks are consistent with those of the standard JCPDS card, and the diffraction peaks are sharp and have no impurity peaks, indicating that different Sr 2+ The PLSBZST ceramics with different doping levels all have perovskite phase structure. 2+ As the doping amount increases, the diffraction peak at (200) shifts to a higher angle, indicating that Sr 2+ According to the Bragg formula: 2dsinθ=nλ (d is the crystal plane spacing, θ is the diffraction angle, and λ is the test wavelength), due to the small ion radius Substitute ions with larger radius It induces lattice distortion, resulting in a decrease in the lattice constant, which is reflected in the XRD spectrum as the diffraction peak moving toward a high angle.

[0046] Figure 2 Pb obtained in Example 1-4 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01Scanning electron microscope (SEM) images of O3 ceramics. Among them, (a) is PLSBZST1, (b) is PLSBZST2, (c) is PLSBZST3, and (d) is PLSBZST4. Figure 2 It can be seen that different Sr 2+ The grain boundaries of PLSBZST ceramics are clear and have a dense microstructure, that is, the grain size distribution is uniform, the grains are closely connected, and there are fewer defects such as pores. The grain size distribution data obtained by ImageJ software analysis shows that the particle size is mainly distributed between 1 and 3 μm. 2+ The average grain size of PLSBZST ceramics increases from 1.61 μm to 1.62 μm with the increase of Sr 2+ As the doping amount continued to increase, the average grain size of PLSBZST ceramics gradually decreased to 1.53 μm, indicating that a certain amount of Sr 2+ The addition of ferroelectrics can inhibit the growth of PLSBZST ceramic grains. The reduction of grain size and the increase of density can improve the breakdown electric field strength of antiferroelectric ceramics, thereby achieving an increase in energy storage density.

[0047] Figure 3 The (Pb 0.92-x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 ) The dielectric constant and dielectric loss of O3 ceramics at 1kHz vary with temperature (a) and PLSBZST2 varies with temperature and frequency (b). The test voltage is 1V and the test frequency is 1kHz. Figure 3 It can be seen from (a) that the relative dielectric constant of PLSBZST ceramics is between 550 and 1000 at room temperature with a frequency of 1kHz. Its value gradually increases with the increase of temperature in the range of room temperature to 150℃. The Curie peaks of all ceramics are relatively wide dielectric constant peaks, rather than traditional sharp dielectric peaks. This is due to the Sn 4+ The random distribution of ion concentration leads to the phase transition from the multi-cell cubic (MCC) phase to the single-cell cubic phase due to the inhomogeneous structure. 2+ The dielectric loss of the PLSBZST ceramics with different doping levels is always kept within 5%. With the increase of temperature, the relative dielectric constant increases slowly and shows a slightly downward trend. The relative dielectric constant of the sample is as low as 650 and as high as 1300. Similar to (PbLa)(ZrSn)O3(PLZS), all ceramics undergo a phase transition from antiferroelectric phase (AFE)-polyhedral cubic phase (MCC)-cubic phase (P) with the increase of temperature. Figure 3 (b) shows the change of dielectric constant of PLSBZST2 with temperature at different test frequencies. It can be seen that the ceramic has good stability in the frequency range of 1 to 50 kHz, and the dielectric loss is always kept within 5%.

[0048] Figure 4 Pb obtained in Example 1-4 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 PE and IE curves of O3 ceramics, where (a) is PLSBZST1, (b) is PLSBZST2, (c) is PLSBZST3, and (d) is PLSBZST4. Figure 4 It can be seen that the electric field value corresponding to the maximum current in the IE curve and the maximum slope change of the PE curve is the antiferroelectric-ferroelectric phase transition electric field of the material. 2+ As the phase transition electric field of the material increases, its E AFE-FE From 311kV / cm to 338kV / cm; E FE-AFE From 295kV / cm to 316kV / cm. According to the tolerance factor formula (R A is the ionic radius of the A site, R B is the ionic radius of the B site, R O O 2- ionic radius), as Sr 2+ As , the antiferroelectric phase stability of the ceramic gradually increases, and the phase transition electric field moves to a higher value.

[0049] Figure 5 Pb obtained in Example 1-4 0.92-x La 0.04 Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 The dischargeable energy density and energy storage efficiency of O3 ceramics under the action of electric field. Among them, (a) is PLSBZST1, (b) is PLSBZST2, (c) is PLSBZST3, and (d) is PLSBZST4. Figure 5 It can be seen that the dischargeable energy density of all ceramics increases with the increase of electric field. When the electric field increases to the antiferroelectric-ferroelectric transition field, the polarization intensity rises rapidly, resulting in a sharp increase in the dischargeable energy density. Figure 6 Pb obtained in Example 1-4 at a frequency of 10 Hz 0.92-x La 0.04Sr x Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 Room temperature PE hysteresis loop of O3 ceramics. Figure 6 It can be seen that different Sr 2+ The polarization intensity of PLSBZST ceramics increases with the increase of electric field. 2+ With the increase of doping amount, the slope of the curve gradually increases in the phase change stage, and the corresponding dielectric constant increases. Figure 7 The different Sr prepared in Examples 1-4 2+ The discharge energy density W obtained by the hysteresis loop of the PLSBZST ceramics under the transition electric field of each component ceramic rec And energy storage efficiency η diagram. Among them, (a) is PLSBZST1, (b) is PLSBZST2, (c) is PLSBZST3, and (d) is PLSBZST4. Figure 7 It can be seen that different Sr 2+ The energy storage efficiency of PLSBZST ceramics is above 85%. 0.84 La 0.04 Sr 0.06 Ba 0.02 Zr 0.64 Sn 0.35 Ti 0.01 O3) Dischargeable energy density W rec Reach 11.16J / cm 3 , while having an energy storage efficiency of 96.23%.

[0050] The present invention adopts the traditional solid phase reaction method, tape casting process and secondary sintering process to synthesize different Sr 2+ The PLSBZST thick film ceramic with a doping amount. According to the X-ray diffractometer (XRD), all components are pure perovskite structures. The scanning electron microscope (SEM) observed that the sintered grain distribution and size of the sample are uniform and dense, with a particle size of 1 to 3 μm. The ceramic group used in the electrical performance test has a dielectric loss of less than 5% in the low temperature range, and the ceramic has good stability in the 1 to 50 kHz frequency range. Among them, Sr 2+ Replace Pb 2+ The bonding mode of Pb has not changed, but its unit cell parameters have changed. Therefore, it can retain a high polarization intensity and increase the transition electric field in the case of a small amount of doping, thereby obtaining a high dischargeable energy density. According to the hysteresis loop, it can be calculated that when x = 0.06, Pb 0.84 La 0.04 Sr 0.06 Ba 0.02 Zr 0.64 Sn0.35 Ti 0.01 The energy storage density of O3 ceramics is 11.16 J / cm 3 The energy storage efficiency is 96.23%. Its high energy storage density and energy storage efficiency have application value in pulse power devices.

[0051] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A high strontium doping zirconium tin lanthanum barium strontium lead titanate ceramic, characterized in that: The molecular formula of the high strontium-doped zirconium-tin-titanate-lanthanum-barium-strontium-lead ceramic is (Pb 0.92-x La 0.04 Sr x Ba 0.02 )(Zr 0.64 Sn 0.35 Ti 0.01 )O3,x=0.04~0.

1.

2. The method for preparing the high strontium doping zirconium tin lanthanum barium strontium lead titanate ceramic according to claim 1, characterized in that: The steps include: S1. PbO, La2O3, SrCO3, BaCO3, ZrO2, SnO2, TiO2 and excess 3-5wt% PbO were wet-milled in a common planetary ball mill, and ethanol and a milling medium were added to obtain a slurry; S2. The slurry is dried at 80 to 120 ° C, sieved after grinding, and then pre-fired at 850 to 950 ° C to obtain a ceramic powder; S3. The ceramic powder is ball-milled, dried and sieved according to steps S1 and S2, and the obtained powder is rolled with octylphenol polyoxyethylene ether and solvent to obtain a premixed slurry; polyvinyl butyral, solvent and trioctyl trimellitate are then added and rolled to obtain a casting slurry with a viscosity of 600 to 800 mPa·s. S4. The casting slurry is placed in a mold, the linear speed of the casting machine film belt is 0.15-0.3 cm / s, the drying temperature is 35-42°C, the binder is removed at 300-600°C, and finally sintered at 1100-1200°C to obtain lanthanum barium strontium lead zirconium tin titanate ceramics, abbreviated as PLSBZST.

3. The method for preparing high strontium-doped zirconium tin lanthanum barium strontium lead titanate ceramics according to claim 2, characterized in that: The ball milling media in step S1 are zirconium dioxide balls with a diameter of 2 to 3 mm and zirconium dioxide balls with a diameter of 4 to 5 mm in a mass ratio of 1:

1.

4. The method for preparing high strontium-doped zirconium-tin-barium-strontium-lead titanate ceramics according to claim 2, characterized in that: The ball milling speed in step S1 is 180-220 rpm, and the ball milling time is 24-48 hours.

5. The method for preparing high strontium-doped zirconium-tin-barium-strontium-lead titanate ceramics according to claim 2, characterized in that: The mesh size of the sieving in step S2 is 40 to 80 meshes, the drying time is 5 to 10 hours, and the pre-burning time is 2 to 3 hours.

6. The method for preparing high strontium-doped zirconium-tin-barium-strontium-lead titanate ceramics according to claim 2, characterized in that: The solvents in step S3 are anhydrous ethanol and butanone in a mass ratio of 1:

1.

7. The method for preparing high strontium-doped zirconium-tin-barium-strontium-lead titanate ceramics according to claim 2, characterized in that: The mass ratio of the powder, octylphenol polyoxyethylene ether, solvent, polyvinyl butyral and trioctyl trimellitate in step S3 is (45-50):(0.8-0.9):(58-60):(5.3-5.5):(1.8-2).

8. The method for preparing high strontium-doped zirconium-tin-barium-strontium-lead titanate lanthanum ceramics according to claim 2, characterized in that: The rotation speed of the rolling mill in step S3 is 100-200 rpm, and the rolling milling time is 18-24 hours.

9. Application of the high strontium doped zirconium tin lanthanum barium strontium lead titanate ceramics according to claim 1 in the field of dielectric energy storage capacitors.

Citation Information

Patent Citations

  • Strontium-doped lead lanthanum zirconate stannate titanate relaxed anti-ferroelectric thick-film ceramic as well as preparation method and application thereof

    CN111470863A

  • Antiferroelectric multilayer ceramic capacitor

    US20090207555A1